Laparoscopic extraction of a symptomatic upper abdominal pedunculated parietal peritoneal lipoma arising intermittent abdominal pain: a case report - Yu Dohmoto; Yoshimasa Akashi; Koichi Ogawa; Tsuyoshi Enomoto; Yusuke Ohara; Yohei Owada; Tatsuya Oda (Journal of Medical Case Reports, 2024)
Abstract Introduction Lipomas arising in the parietal peritoneum are rare, and some of them cause abdominal pain due to torsion of the pedunculated peritoneum. We encountered a case of parietal peritoneal lipoma arising upper peritoneum. In this report, we describe the detail of clinical presentation and discuss its potential pathogenesis and treatment strategy. Case presentation 45 year-old Japanese female patient presented with long-lasting intermittent pain in the left upper abdominal region. Abdominal imaging showed a well-defined fatty mass measuring 40 mm in size, suggesting a parietal peritoneal lipoma. Laparoscopy revealed a tumor with a twisted peduncle; however, no adhesion of the surrounding tissues and ischemic changes were visible. The tumor was easily removed by dissection of the tumor pedicle. Conclusion Parietal peritoneal lipoma often shows pedunculated form and it causes abdominal pain by the torsion of tumor pedicle. Therefore, this type of lipoma should be considered a more aggressive surgery.